PANDANGAN ASSOCIATION OF SOUTHEAST ASIAN NATIONS (ASEAN) TERHADAP ANCAMAN TERORISME DI ASIA TENGGARA - Rahil Lailatul Jannah; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ASEAN is the organization that oversees the countries in the Southeast Asian region. ASEAN plays an important role in promoting regional peace and stability, one of the issues that threatens the security stability of countries in the Southeast Asian region, namely terrorism. The purpose of this study is to find out how ASEAN views the threat of terrorism in Southeast Asia with the establishment of the ASEAN Convention on Counter Terrorism (ACCT). The method used in this study is descriptive qualitative with data sourced from books, journals and other literature. The results of the study showed that ASEAN views terrorism as a real threat to the regional security of Southeast Asia and makes the issue of terrorism a security agenda that must be eradicated so that regional security stability is well maintained, therefore ASEAN seeks to tackle terrorism by forming the ASEAN Convention on Counter Terrorism (ACCT). Keywords: ASEAN, Terrorism, ASEAN Convention on Counter Terrorism (ACCT), Threat